Bimbingan Keagamaan di Daerah Pesisir - Ineu Inayah; Mu'minatul Zanah; Hajir Tajiri (Department of Islamic Guidance and Counseling, Faculty of Dakwah and Communication, UIN Sunan Gunung Djati Bandung, 2017)
The research is purpose; first, to know the religious condition in seaboard of Muaragembong, Second, to know the implementations of religious guidance in society of muaragembong seaboard, third, to know the result of religious guidance in society of muaragembong seaboard. The research is using descriptive method by qualitative approach, that is systematically describing and accurately about condition of religious and implementation of religious guidance in seaboard of Pantai Bahagia village, Muaragembong subdistrict of Bekasi regency. Technique of collecting data in this research by observation, interview, and literature study. The result of research, the condition of religious is Islam majority, the religious activity that is weekly and monthly study of religious, Friday take pray, pray together, tahlil, aqiqah, reciting of Yasin verse, and commemorating red-letter days of Islam, in addition to that, there are any fisher ceremony in every year who called commonly as sea party, or Nadran (native culture) by religious ritual. The implementation of religious by directly method every day after pray together, one week is mothers and fathers religious study, one month on fourth week is general study of religious, and every one year is the ceremony of fishers. By looked be present the quantity of jama’ah, the quality of people comprehension to Islam, increasingly by result of interview about it, nowdays the society be conviced about their requirement of religious spirituality. Tujuan penelitian ini ialah mengetahui kondisi keagamaan di daerah pesisir muaragembong, mengetahui pelaksanaan bimbingan keagamaan di masyarakat daerah pesisir muaragembong, mengetahui hasil bimbingan keagamaan di masyarakat daerah pesisir muaragembong. Metode penelitian menggunakan metode deskriptif dengan pendekatan kualitatif yakni menggambarkan secara sistematis dan akurat tentang kondisi keagamaan dan pelaksanaan bimbingan keagamaan di daerah pesisir desa pantai bahagia kecamatan Muaragembong Kabupaten Bekasi. Tekhnik pengumpulan data dalam penelitian ini dilakukan dengan cara observasi, wawancara, dokumentasi, dan studi kepustakaan. Hasil penelitian, kondisi keagamaan mayoritas beragama islam, kegiatan keagamaan yang ada yaitu pengajian mingguan, pengajian bulanan, sholat jum’at, sholat berjama’ah, tahlilan, aqiqahan, yasinan, dan memperingati hari-hari besar Islam, selain itu juga adanya syukuran para nelayan setiap tahun yang biasa disebut pesta laut atau kebudayaan leluhur (nadran) yang di sertai dengan ritual keagamaan. Pelaksanaan keagamaan dengan metode secara langsung dilaksanakan setiap hari setelah sholat berjama’ah, satu minggu sekali pengajian ibu-ibu dan bapak-bapak, satu bulan sekali pada minggu ke empat pengajian umum, dan satu tahun sekali untuk syukuran para nelayan. Di lihat dari banyaknya jama’ah yang hadir, secara kualitas pemahaman masyarakat terhadap ajaran Islam semakin meningkat. hasil dari wawancara mengenai hal tersebut, masyarakat kini meyakini akan kebutuhan spiritual keagamaannya.